ANALISIS TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG PENATALAKSANAAN DISMENORE DI DUSUN PRINGGOLAYAN BANTUL JANUARI - FEBRUARY 2024 - Yulianto, Danang; Vita, Vita (Jurusan Farmasi, Politeknik Kesehatan Kementerian Kesehatan Aceh, 2024)
The incidence of dysmenorrhea in Indonesia is quite high, with primary type dysmenorrhea around 54.89%. Adolescents' knowledge is much needed in carrying out appropriate management of dysmenorrhea to improve their quality of life. The majority of adolescents girls knowledge about the management of dysmenorrhea is still in the poor category. The aim of this research was to determine the knowledga level of adolescents girls about management of dysmenorrhea in Pringgolayan Hamlet, Bantul. The method used in this research is descriptive observational using the purposive sampling method with 100 respondents from 1,464 people of population. Data were collected using a questionnaire containing the definition, signs and symptoms, risk factors and management of dysmenorrhea. The data was then analyzed descriptively to describing knowledge in a situation with good, sufficient and poor levels of knowledge. The results of this research are the level of knowledge of adolecent girls in Pringgolayan Hamlet, Bantul, which is in the good category with 18 respondents (18%), the sufficient category with 50 respondents (50%) and the poor category with 32 respondents (32%). The conclusion of this research is that the level of knowledge of adolescent girl in Pringgolayan Hamlet, Bantul is included in the sufficient category. Keywords: Dysmenorrhea, Level of Knowledge, Adolescent Girls